EFFECTIVE STRATEGIES FOR LEARNING ENGLISH SYNTAX (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This thesis investigates effective strategies for learning English syntax. It emphasizes various methods and techniques that can enhance the understanding and application of syntactical rules in English. The research explores instructional strategies, practical exercises, and technology-assisted tools that support syntax acquisition and mastery. The goal is to provide educators and learners with actionable insights for improving syntax learning outcomes.